Marine proteins and peptides biological activities and applications - Kim, Se-Kwon.; ebrary, Inc. (Chichester [England] : John Wiley & Sons Inc., 2013)
"This book will provide cutting edge content on both the human health benefits of marine proteins and peptides, and their industrial applications"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Marine pharmacology; Marine biology; Electronic books